UPAYA MENINGKATKAN HASIL BELAJAR SISWAMATA PELAJARAN MATEMATIKA MATERI PERKALIANDAN PEMBAGIAN PECAHAN MELALUI METODE COOPERATIF LEARNING MODEL TGTKELAS VI SD NEGERI 1 KEDIRI - Bambang Sulistiono (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
The class action done by the researcher in this research is the useof Coorperation Learning model of TGT in Grade VI SD Negeri 1 Kediri. Thefindings of this TOD result is the improvement of student learning outcomesafter applying the TGT learning model from the initial average condition ofclass 62,69, the average cycle I 66,53 and the average cycle II 76,92. Then forclassical completeness from initial condition 46.15%, cycle I 53.85% and in cycleII to 76.92%. There is an increase, especially the classical completeness from theinitial to the first cycle is 7.7%, cycle I to cycle II is 23.07%.